Batas Usia Kedewasaan Dalam Transaksi E-Commerce - Veronica Andriani (SAPIENTIA ET VIRTUS, 2019)
E-Commerce is a new way for buying and selling transactions, where these transactions are carried out online to facilitate and reach everyone without a certain geographical limit. In addition to e-commerce goodness, it has a weakness that the identity of the stakeholder that cannot be known. The importance of information related to identity is needed to determine whether the parties to the transaction are capable in carrying out legal actions. This becomes important to know which benchmarks of adults can conduct transactions online.